ANALYSIS, CONCEPT OF STATE AND EDUCATION CENTRALIZED EDUCATION AND SCHOOL-BASED MANAGEMENT - Ayu Indriasih; Firman; Riska Ahmad (Literasi Nusantara, 2021)
Education is an important part in a country where education plays a big role as a forum for creating intelligent and noble sons and daughters of the nation. The state refers to an area or region that exists on the surface of the earth, there is a government that regulates the economy, politics, social, culture, defense and security and so on. The state is also a tool (agency) of the community that has the power to regulate human relations in society and regulate the phenomenon of power in society. Centralization is important in the ownership of central authority related to education to become the reference point of education itself. Decentralization is more about acknowledging that the education process will not work well when everything is controlled from the center. In an effort to maximize the implementation of decentralized education, the concept of school-based management is now being developed, which seeks to increase the role of schools and surrounding communities (stakeholders) in education management.